PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PT. NYONYA MENEER SEMARANG (STUDI KASUS PADA KONSUMEN JAMU HABIS BERSALIN) - Ruth Suharyati; Sudharto Prawoto Hadi; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2013)
PT. Nyonya Meneer is one of medicinal herbs company in Indonesia. PT. Nyonya Meneer always consistent in keep of quality, that is supply medicinal herbs product which good quality and can satisfy hope of customers. PT. Nyonya Meneer have many challenge and rival, specifically competition and turn up of new products of rivals, so that PT. Nyonya Meneer must have many innovation and produce product which appropriate with need of people so that customer will be satisfy to product. This research aim to know influence of product quality, price and customers satisvaction.Research Type which used in this research is explanatory research. Interpretation of sample technique had used sampling purposive method, that is determining of sample with certain opinion which is sample have classification : respondent is costumer of jamu habis bersalin, Nyonya Meneer product had used this product as many as two or more, have ages minimal 17 years and can answer question of interview. Then, total of sample is 100 respondent. The data analysis technique which used in this research is qualitative analysis and quantitative analysis which used Validity Trial, Reability Trial, Simple Linier Regresssion, Double Linier Regresssion, T Trial, F Trial and determinant coefficient had used SPSS.The result of research indicate that product quality of jamu habis bersalin Nyonya Meneer belonging to quality and price of product belonging to cheap so that customers has satisfied. The result of analysis prove in a partial great of influence product quality to customers satisvaction is 43.4%, influence price to customers satisvaction is 63.3% and in a simultaneous great of influence quality product and price to customers satisvaction is 64,9%. Therefore, PT. Nyonya Meneer must increase product quality that is increase of benefit jamu habis bersalin product and strive for price of product is achievable for customer. So that customers satisvaction of jamu habis bersalin Nyonya Meneer will be increase.